2005
DOI: 10.1007/s11083-005-9008-7
|View full text |Cite
|
Sign up to set email alerts
|

The Prism Over the Middle-levels Graph is Hamiltonian

Abstract: Let B k be the bipartite graph defined by the subsets of {1, . . . , 2k + 1} of size k and k + 1. We prove that the prism over B k is hamiltonian. We also show that B k has a closed spanning 2-trail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The existence proof in [7] does not attempt to estimate c. To improve the bound in Theorem 1 for, say all k < 5600, would require a value of c < 10. On the other hand, it has been shown that M 2k+1 has a closed spanning walk in which no edge and no vertex occurs more than twice [5].…”
Section: Introductionmentioning
confidence: 99%
“…The existence proof in [7] does not attempt to estimate c. To improve the bound in Theorem 1 for, say all k < 5600, would require a value of c < 10. On the other hand, it has been shown that M 2k+1 has a closed spanning walk in which no edge and no vertex occurs more than twice [5].…”
Section: Introductionmentioning
confidence: 99%
“…In [15] we proved that the middle-levels graph is prism-hamiltonian. Nash-Williams [20] conjectured that 4-connected, 4-regular graphs are hamiltonian.…”
Section: Problem 1 Let G Be a Graph Of Order N And Let X And Y Be Twmentioning
confidence: 92%
“…Savage and Winkler [15] showed that B k has a cycle containing at least 86.7% of the graph vertices, for k ≥ 19. Horák, Kaiser, Rosenfeld and Ryjáček [7] showed the middle levels graph has a closed spanning 2-trail. It remains open to prove similar results for the odd graphs.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%
“…Horák, Kaiser, Rosenfeld and Ryjáček [7] showed that the prism over the middle levels graph is Hamiltonian, and consequently B k has a closed spanning 2-trail. Savage and Winkler [15] showed that if B k has a Hamiltonian cycle for k ≤ h, then B k has a cycle containing a fraction 1 − ε of the graph vertices for all k, where ε is a function of h. For example, since B k has a Hamiltonian cycle for 2 ≤ k ≤ 18, then B k has a cycle containing at least 86.7% of the graph vertices, for any k ≥ 2.…”
Section: Introductionmentioning
confidence: 99%